2021
DOI: 10.3390/ijerph18083867
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Resilience of Nursing, Optometry, Radiography and Medical Laboratory Science Students

Abstract: Background: The concern over the high level of stress experienced by students of the caring professions has led to increased attention being paid to the promotion of their resilience. Most earlier studies have focused on the resilience of medical and nursing students. There has been little exploration of the resilience and associated factors of students of other health-care disciplines. The aim of this study was to gather data from students of pre-registration health-care disciplines to identify the factors th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 71 publications
(66 reference statements)
0
12
0
Order By: Relevance
“…Some demographic characteristics have been shown to affect resilience in nursing students, including inadequate income (Ching & Cheung, 2021 ; Ertekin Pinar et al, 2018 ; Hamadeh Kerbage et al, 2021 ; Yıldırım et al, 2021 ; Yıldız, 2021 ), age (Ching & Cheung, 2021 ; Ertekin Pinar et al, 2018 ; Hasson et al, 2021 ), gender (Arries‐Kleyenstüber, 2021 ; Ching & Cheung, 2021 ), marital status (Yıldırım et al, 2021 ), year of study (Elzohary et al, 2017 ; Fernández‐Martínez et al, 2021 ; Yıldırım et al, 2021 ), religion (Sigalit et al, 2017 ) and living conditions (Yıldırım et al, 2021 ). However, some have argued that age does not affect resilience (Arries‐Kleyenstüber, 2021 ; Grande et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some demographic characteristics have been shown to affect resilience in nursing students, including inadequate income (Ching & Cheung, 2021 ; Ertekin Pinar et al, 2018 ; Hamadeh Kerbage et al, 2021 ; Yıldırım et al, 2021 ; Yıldız, 2021 ), age (Ching & Cheung, 2021 ; Ertekin Pinar et al, 2018 ; Hasson et al, 2021 ), gender (Arries‐Kleyenstüber, 2021 ; Ching & Cheung, 2021 ), marital status (Yıldırım et al, 2021 ), year of study (Elzohary et al, 2017 ; Fernández‐Martínez et al, 2021 ; Yıldırım et al, 2021 ), religion (Sigalit et al, 2017 ) and living conditions (Yıldırım et al, 2021 ). However, some have argued that age does not affect resilience (Arries‐Kleyenstüber, 2021 ; Grande et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Maintaining a good work and life balance is one of the progressing issues academics face in higher education institutions [52]. Ching & Cheung [53] found that having a paid job predicted resilience. Working aids in developing resilience by fostering competence in the face of, and professional growth following, workplace adversity [54].…”
Section: Independent Variablesmentioning
confidence: 99%
“…Often health-profession students, put patients' needs before their own, leading to an underreporting of mental health conditions in health-profession students (8). Wellbeing of health-profession students has also been found to be negatively impacted by the time demands of the course and the perceived difficulty of the course work (8). The power-distance nature of undergraduate students' interactions and relationships with clinical supervisors, is also perceived to cause stress (9).…”
Section: Introductionmentioning
confidence: 99%
“…The transition to university life amongst first year students forces the development of social skills, responsibility and learning to cope without family and friends. Moreover, stress caused from expected academic performance as well as time pressures tests, required grades, higher standard of academic work and anxieties about future job opportunities (5, 8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation